Countering Radicalism: The Case of Front Jihad Islam in Asahan Regency, North Sumatra" - Muhammad Faisal Amri (Sufiya Journal of Islamic Studies, 2026)
Religious radicalism is a social phenomenon that continues to be a serious concern in religious life in Indonesia. Narrow and textual religious understandings often give birth to exclusive attitudes that have the potential to lead to radicalism. Therefore, deradicalization efforts need to be carried out comprehensively, one of which is through strengthening faith. This article aims to analyze the strengthening of faith as a deradicalization strategy carried out by the Regional Leadership Council of the Islamic Jihad Front (DPD FJI) in Asahan Regency. This study uses a qualitative approach with a case study method. Data was collected through interviews, observations, and documentation of da'wah activities and religious guidance carried out by DPD FJI. The results of the study show that the strengthening of the faith carried out systematically through Islamic studies, the development of the ummah, and a persuasive approach is able to form a more moderate religious understanding and reduce the potential for the development of radical ideas in society. Thus, local Islamic organizations have a strategic role in efforts to deradicalize based on Islamic faith values that are rahmatan lil 'alamin.